THE COMPARISON BETWEEN THE MOVIE OF MULAN 1998 AND ITS REMAKE, MULAN 2020 (A COMPARATIVE LITERATURE STUDY) - Irsya Syafinah; Endang Susilowati (Universitas Ngudi Waluyo, 2021)
This paper title is The Comparison between The movie of Mulan 1998 and its remake,Mulan 2020. The objectives of this paper are to find out the similarities and the differencesin intrinsic elements of both literary works. This research used comparative theory toanalyze the reduction, addition, and modification. This research also used descriptivequalitative, data collected from the intrinsic elements of both movies. In collecting data,the researcher used description as the instrument to find out the reduction, addition,and modification of Mulan 1998 and Mulan 2020. In this research, the researcher foundthat there were several differences and similarities in intrinsic and extrinsic elements.Additionally, the researcher found that reduction, addition, and modification influencedthe change of some intrinsic elements in both movie versions.